Effects of a 24-week exercise program on anthropometric, body composition, metabolic status, cardiovascular response, and neuromuscular capacity, in individuals with intellectual and developmental disabilities - Jacinto, Miguel; Matos, Rui; Monteiro, Diogo; Antunes, Raul; Caseiro, André; Gomes, Beatriz; Campos, Maria João; Ferreira, José Pedro (Frontiers in Physiology, 2023)
The prevalence of overweight and obesity has increased in the last decades, including in people with Intellectual and Developmental Disabilities (IDD). This is even more concerning when it is globally accepted that a low physical condition contributes to the deterioration of functionality and increases the risk of developing chronic diseases during life, with effective implications for health and well-being. The aim of the present study is to investigate the effects of two physical exercise intervention programs on institutionalized individuals with IDD. Twenty-one adults with IDD (43.04 ± 11.18 years) were split by convenience into three groups: i) an indoor training group (IG; N=7; 24-week machine-based gym intervention), ii) an outdoor training group (OG; N=7; 24-week outdoor intervention with low-content materials), and iii) a control group (CG; N=7). Assessed outcomes included indicators of health and neuromuscular capacity. The ShapiroWilk (n<50) and Levene tests were used to verify data normality and homoscedasticity. A Kruskal-Walli test was performed to understand if there were differences between the groups. For comparison purposes and to assess hypothetical differences between groups, the Wilcoxon signed-rank test and the Friedman test were used. The respective effect size was calculated, and the significance level was defined at 0.05. There was a difference in fat mass in OG (initial ≠ intermediate; Bonferroni corrected: t=2.405; p=0.048; W=0.08 and initial ≠ final moments; Bonferroni corrected: t=2.405; p=0.048; W=0.08). Indoor intervention programs seem to be more effective than outdoor intervention programs for reducing heart rate rest (t=-2.912; p=0.011; W=-0.104), when compared with CG. A low-cost outdoor intervention in contact with nature appears to be more effective for fat mass reduction. The results for heart rate variability are not clear and robust. Finally, an indoor intervention using weight-training machines appears to be a good method to promote neuromuscular capacity.